Modeling of Taxation that Considers Reproduction - Kravets, Tetyana (Ekonomika, 2008)
The article considers the modifications of taxation models that define the influence of tax rate on the production growth and the minimal net margin. The aim of the article is to analyse the development of taxation models that combine total tax allocation and value added, remuneration of labour, amortization. The models generalize the introduction of figurers’, heterogeneity and the production function complication, namely the two-factor production function while considering capital and labour is used. As a result, the estimation of the production growth depending on the tax rate was established, the minimal net margin that allows simple reproduction was defined, the total tax allocation frontier was found. A tax rate optimization model that maximizes allocation to the budget was considered. Calculations for Ukrainian macroeconomic data were conducted. Statistic estimations of the model’s main macroeconomic components allow defining the potential level of the economic growth, comparing it with the actual growth, and concluding on the efficiency of the national development model.